Gemtuzumab ozogamicin for relapsed or primary refractory acute myeloid leukemia in children—the Polish Pediatric Leukemia and Lymphoma Study Group experience - Pawinska-Wasikowska, Katarzyna; Czogala, Malgorzata; Skoczen, Szymon; Surman, Marta; Rygielska, Monika; Ksiazek, Teofila; Pac, Agnieszka; Wieczorek, Aleksandra; Skalska-Sadowska, Jolanta; Samborska, Magdalena; Wachowiak, Jacek; Chaber, Radoslaw; et al. (Frontiers in Immunology, 2023)
Background: Gemtuzumab ozogamicin (GO), one of the first targeted drug used in oncology, consists of an anti-CD33 monoclonal antibody bound to a derivative of cytotoxic calicheamicin. After the drug withdrawn in 2010 due to a significantly higher rate of early deaths, GO regained approval in 2017 for the treatment of newly diagnosed, refractory, or relapsed acute myeloid leukemia (AML) in adults and children over 15 years of age. The objective of the study was a retrospective analysis of clinical characteristics, treatment outcomes, and GO toxicity profile in children with primary refractory or relapsed AML (R/R) treated in Poland from 2008 to 2022.